Growing lettuce seedlings in different organic composts used as substrate - Sousa, Edilara Leandro de; Silva, Karolina Flôres da; Shipitoski, Ricardo Moraes; Nardis, Bárbara Olinda; Silva, Jodean Alves da; Araújo, Lourismar Martins; Lanssanova, Luciano Rodrigo; Andrade, Fabrício Ribeiro (Comunicata Scientiae, 2024)
Lettuce is the most important vegetable in the world and the most consumed in Brazil. Seedling production with a good quality substrate is very important in the lettuce crop production process. The objective of this study was to evaluate the performance of organic compost substrates in the production of lettuce seedlings. The experiment was carried out in a greenhouse, using polyethylene trays containing 128 trapezoidal cells in a completely randomized design with a 5 × 2 factorial scheme consisting of 5 substrates (commercial substrate; compost I; compost II; compost III; compost IV) and P2O5 supplementation (absent and 0.525 kg m−3 P2O5) and 4 replications. Substrates were produced by composting agro-industrial waste: sawdust, wood shavings and residues from a restaurant, pig litter, cattle manure, residues from the shoot and tubers of sweet potato, soybean residue, and drained bovine ruminal residue. The emergence, plant height, number of leaves, fresh root and shoot biomass, and clod stability of the substrate were evaluated. The substrate formulated from pig litter, cattle manure, and sweet potato (compost II) and pig litter and drained bovine ruminal residue (compost IV) formed seedlings with a greater clod stability of the substrate, plant height, number of leaves, and fresh root and shoot biomass. Substrates based on composting pig litter, cattle manure, and sweet potato (composts II) and pig litter and drained bovine ruminal residue (compost IV) were most suitable for producing lettuce seedlings.